The Detection of Lumpy Skin Disease Virus Infection by Clinical Findings and PCR Method in Turkey - Gurcay, Metin; Sait, Ahmet; Parmaksiz, Ayse; Kilic, Ayse (Kafkas Univ, Veteriner Fakultesi Dergisi, 2015)
Lumpy Skin Disease (LSD) is a viral disease of cattle, buffalo and some wild species characterized by oedema and nodules on the skin. The aim of this study was to report the presence and the clinical signs of LSD in infected cattle in Turkey, and to confirm by PCR method. For this purpose, 113 cattle showing clinical signs of LSD were examined from 8 settled farms in Turkey between September 2013 to June 2014. Then, 12 skin nodule samples from these cattle were obtained, and brought to the virology laboratory. The samples were tested by PCR according to the method described by OIE. The clinical diagnosis was well correlated with PCR results.
Türkiye’de Lumpy Skin Disease Virus Enfeksiyonunun Klinik Bulgular ve PCR Yöntemi İle Saptanması
Keywords: Lumpy Skin Disease; PCR; Epidemiology